2021
DOI: 10.5114/amscd.2021.105843
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone score and 3D-DXA in young, antiretroviral treatment-naïve patients in Madrid

Abstract: IntroductionLow bone mineral density (BMD) has been described as a non-AIDS-related event in human immunodeficiency virus (HIV)-patients, but it is poorly studied by dual-energy X-ray absorptiometry (DXA) and trabecular bone score (TBS) in young HIV-infected men who have received no previous antiretroviral treatment (ART).Material and methodsA retrospective study of 56 naïve-HIV-infected men under 50 years old with recently diagnosed HIV infection, between May 2012 and July 2017.ResultsThe mean age was 33.11 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Seto et al [ 46 ] also demonstrated that TAF is associated with a superior bone safety profile than that of TDF at more than 96 weeks of treatment, even in patients with risk factors associated with bone loss and higher initial FRAX scores. Our study demonstrates that these bone changes are observed even earlier, at the beginning of treatment (12 weeks), and in adult patients younger than 50 years, a population with a high rate of bone affectation even before treatment initiation [ 8 , 47 - 49 ]. Therefore, PLHIV of all ages may potentially benefit from avoiding therapies containing TDF, which has repeatedly been shown to cause BMD loss [ 16 , 26 , 48 , 50 - 52 ] .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Seto et al [ 46 ] also demonstrated that TAF is associated with a superior bone safety profile than that of TDF at more than 96 weeks of treatment, even in patients with risk factors associated with bone loss and higher initial FRAX scores. Our study demonstrates that these bone changes are observed even earlier, at the beginning of treatment (12 weeks), and in adult patients younger than 50 years, a population with a high rate of bone affectation even before treatment initiation [ 8 , 47 - 49 ]. Therefore, PLHIV of all ages may potentially benefit from avoiding therapies containing TDF, which has repeatedly been shown to cause BMD loss [ 16 , 26 , 48 , 50 - 52 ] .…”
Section: Discussionmentioning
confidence: 93%
“…Both the risk factors associated with HIV infection (malnutrition, low body weight, high tobacco and alcohol consumption, and low levels of vitamin D) and the disease itself induce bone remodeling through a complex interaction of T cells with osteoclasts and osteoblasts. In adults [ 3 , 5 - 8 ], a decrease in BMD has also been associated with prolonged antiretroviral treatment, principally tenofovir disoproxil fumarate (TDF), indicating that the initial loss of BMD after beginning cART may be due to effects of the medication [ 5 , 6 ]. However, several studies have shown bone damage in therapy-naïve HIV-infected patients [ 3 , 9 , 10 ], cases in which the main guidelines do not specifically recommend evaluating BMD [ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%